Pengembangan Pendidikan Karakter Berbasis Nilai-Nilai Islam Sebagai Solusi Untuk Mengatasi Kenakalan Remaja di Sekolah Menengah - Ermawita Ermawita; Juliati Juliati; Halisnawati Halisnawati (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
Character education based on Islamic values plays a crucial role in shaping the behavior and morals of adolescents, especially in secondary schools, which are often faced with the phenomenon of juvenile delinquency. Juvenile delinquency in secondary schools, such as bullying, drug abuse, and brawls, poses a significant challenge in moral and social education. In this context, the implementation of character education based on Islamic values can be an effective solution to address these issues. Islamic values, such as honesty, discipline, responsibility, and compassion, can be instilled in students' daily lives through learning, role models, and extracurricular activities. This approach is expected to shape adolescents who excel not only academically but also possess good character, discipline, and responsibility in their personal and social interactions. Character education based on Islamic principles offers students a comprehensive moral framework, helping them navigate the challenges of adolescence in a more constructive way. This study aims to explore the potential of character education based on Islamic values in overcoming juvenile delinquency in secondary schools. The methods used include a literature review and observation of the implementation of character education in several secondary schools. The results indicate that strengthening character education based on Islamic values has a positive impact, as students become more responsible, empathetic, and socially aware. Therefore, the implementation of character education based on Islamic values in secondary schools is essential in shaping a generation that is morally upright and prepared to face global challenges.